Pore structure expansion and evolution in sandstone with prefabricated crack under freeze-thaw cycles based on CT scanning - Zhang, Xinting; Luo, Xuedong; He, Xu; Niu, Shuaishuai (Frontiers in Earth Science, 2024)
In cold regions, rocks undergo periodic temperature fluctuations, resulting in deterioration in pore structure and mechanical behavior. This degradation can lead to instability in rock masses and contribute to landslides. While many studies have investigated the effects of freeze-thaw (F-T) cycles on the mechanical behavior of rocks, the micro-level mechanisms of deterioration remain less understood. In this study, the evolution of the pore structure of a prefabricated sandstone with 30 freeze-thaw cycles ranging from -20°C to 20°C is explored using CT scanning. The influence of the prefabricated crack is highlighted. The results indicate a significant impact of freeze-thaw cycles on large pores, with their proportion increasing from 15.28% to 38.72% after 30 F-T cycles. Within the initial 10 F-T cycles, pore structure changes occur without the expansion of prefabricated crack. However, after 15 F-T cycles, prefabricated crack begins extending downward, eventually becoming nearly continuous after 30 F-T cycles. Prefabricated crack notably influences pore distribution during freeze-thaw cycles, with higher porosity near the fracture, where pores initially expand and connect. These findings provide insights into the damage mechanism in sandstone under F-T cycles.